2012
DOI: 10.1111/j.1755-5949.2012.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of Association between Particulate Matter and Stroke Attack

Abstract: We found some evidence for an effect of air pollutants on stroke attack risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Generally, the magnitude of our estimates was comparable with previous findings worldwide. 22 In the Netherlands, for example, Hoek et al reported that a 10 μg/m 3 increase of PM 10 , SO 2 , and NO 2 was associated with 0.4%, 1.3%, and 1.6% increase of stroke mortality, though the associations were significant for SO 2 only. 23 In another study in Seoul, Korea, Hong et al estimated a 0.7% (95% confidence interval, 0.6-0.9) increase in stroke mortality per 10 μg/m 3 of PM 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the magnitude of our estimates was comparable with previous findings worldwide. 22 In the Netherlands, for example, Hoek et al reported that a 10 μg/m 3 increase of PM 10 , SO 2 , and NO 2 was associated with 0.4%, 1.3%, and 1.6% increase of stroke mortality, though the associations were significant for SO 2 only. 23 In another study in Seoul, Korea, Hong et al estimated a 0.7% (95% confidence interval, 0.6-0.9) increase in stroke mortality per 10 μg/m 3 of PM 10 .…”
Section: Discussionmentioning
confidence: 99%
“…1219 The literature yields few systematic reviews and meta-analyses of PM 2.5 -related strokes in particular. This study is distinct from recently published meta-analyses in 2 ways: first, it uses a novel statistical approach and second, it is designed to directly inform air pollution risk assessments.…”
mentioning
confidence: 99%
“… 18 Another meta-analysis showed that fine particulate matter ≤10 µm (PM10) and PM2.5 concentrations increased the risk of stroke and heart attack. 19 A review article found that several groups, including elderly subjects, patients with diabetes mellitus and patients with coronary artery disease, appeared to be particularly sensitive to the harmful effects that resulted from exposure to particulate matter. 20 Strong relationships between myocardial infarction and/or stroke were found in nine of 14 studies related to PM10 and in two of five studies related to PM2.5.…”
Section: Introductionmentioning
confidence: 99%